2000
DOI: 10.1146/annurev.bioeng.2.1.339
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Engineering

Abstract: Antibodies are unique in their high affinity and specificity for a binding partner, a quality that has made them one of the most useful molecules for biotechnology and biomedical applications. The field of antibody engineering has changed rapidly in the past 10 years, fueled by novel technologies for the in vitro isolation of antibodies from combinatorial libraries and their functional expression in bacteria. This review presents an overview of the methods available for the de novo generation of human antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
142
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(150 citation statements)
references
References 216 publications
4
142
1
3
Order By: Relevance
“…Both primers (upstream primer, 5Ј-CCA TGG GCC CAA GCT TTG CAA AGA TGG ATA AAG-3Ј; downstream primer, 5Ј-TTT GGG CCC GAA GAA CCG CCA CCA CCA GAA CCG CCT CCA CCA GAG CCA CCA CCA CCA GGC CTG ATC TCT TTT TTT GGG TTT GGT G-3Ј) contain an ApaI site suitable for cloning the Gal4 activation domain including the SV40 T-antigen nuclear localization signal N-terminal to the different scFvs in the context of pESBA-Act (15). The activation domain and the single-chain antibodies are separated by a (GGGS) 3 linker encoded by the downstream primer. All clones were sequenced to confirm in-frame fusion with the Gal4 activation domain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both primers (upstream primer, 5Ј-CCA TGG GCC CAA GCT TTG CAA AGA TGG ATA AAG-3Ј; downstream primer, 5Ј-TTT GGG CCC GAA GAA CCG CCA CCA CCA GAA CCG CCT CCA CCA GAG CCA CCA CCA CCA GGC CTG ATC TCT TTT TTT GGG TTT GGT G-3Ј) contain an ApaI site suitable for cloning the Gal4 activation domain including the SV40 T-antigen nuclear localization signal N-terminal to the different scFvs in the context of pESBA-Act (15). The activation domain and the single-chain antibodies are separated by a (GGGS) 3 linker encoded by the downstream primer. All clones were sequenced to confirm in-frame fusion with the Gal4 activation domain.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting PCR product was digested with EcoRI and cloned into plex113 (18) cut with EcoRI. The leucine zipper of the human c-Jun protein (Swiss-Prot accession number P05412, amino acids 274 -314) was generated by PCR from plasmid pAB140 3 with the primers 5Ј-CGG GGA TCC ACC GCA TCG CTG CCT CCA AGT G-3Ј and 5Ј-GCT CTA GAG CTC AAA ATG TTT GCA ACT GCT GCG TTA G-3Ј carrying a BamHI and XbaI site, respectively. The DNA fragment was digested with the appropriate enzymes and cloned into BamHI-and XbaI-digested plex113 (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments and theory have emphasized that recombination and gene transfer in various forms increase the rate of laboratory directed protein evolution [4,5,6] (for reviews see [7,8]). Other experiments have amplified this point and have also suggested that, while significant in practice, the advantage of recombination may simply be to speed up the evolutionary process that would naturally occur by mutation alone in the limit of a long enough evolutionary time or a large enough population size [9,10,11].The Eigen [12] and Crow-Kimura [13], or parallel, models of viral quasispecies evolution are among the simplest that capture the basic processes of mutation, selection, and replication that occur in natural evolution. These mathematical models exhibit phase transitions, such that for mutation rates below critical values, an identifiable quasispecies forms.…”
mentioning
confidence: 99%
“…There is a great interest in developing smaller versions of therapeutic antibodies for several reasons: namely to improve tumor penetration, eliminate the humanization process, and reduce the cost of production (Maynard and Georgiou, 2000;Hudson and Souriau, 2003). Previously, we established a general principle that a single CDR3 loop from the heavy chain of an antibody is sufficient to mimic its parental monoclonal antibody function (Murali and Greene, 1998).…”
Section: Introductionmentioning
confidence: 99%